La conquista del Caucaso nella letteratura russa dell'Ottocento Puškin, Lermontov, Tolstoj - Magarotto, Luigi (Biblioteca di Studi Slavistici, 2015)
The author addresses the issue of the conquest of Caucasus at the hand of the Tsarist army, investigating the attitude held towards this event by three of the major authors of nineteenth-century Russian literature: Aleksandr Puškin (1799-1837), Mikhail Lermontov (1814-1841) and Leo Tolstoy (1828-1910), expressed through some of their most famous works. As for Puškin, the analysis touches the three main Southern Poems, as well as the account of his trip to Arzrum in 1829 on the Russian-Turkish war theatre, and the drama Boris Godunov, dedicated above all to the matter of power, in which however the will to create an empire imposes itself. The analysis of Lermontov's works, in addition to the poem The novice, set in Georgia, is also about the short story Bela, which is part of the 'novel' A hero of our time. The short story was chosen for its clear display of the Russian officers' attitude of contempt towards the indigenous Caucasians. The analysis of Tolstoy starts with the young author's position in the 1850s, when he was a voluntary fighter in the Caucasus, as shown in the story The raid. Then, the analysis moves to the position of the 'mature' Tolstoy, a pacifist and anti-militarist, who expresses his ideas in the long story Hadji Murat.